Whose money, whose time? A nonparametric approach to modeling time spent on housework - Sanjiv Gupta; Michael Ash (University of Massachusetts, Department of Economics, 2006)
We argue that earlier quantitative research on the relationship between heterosexual partners' earnings and time spent on housework has two basic flaws. First, it has focused on the effects of women's shares of couples' total earnings on their housework, and has not considered the simpler possibility of an association between women's absolute earnings and housework. Consequently it has relied on unsupported theoretical restrictions in the modeling. We adopt a flexible, nonparametric approach that does not impose the polynomial specifications on the data that characterize the two dominant models of the relationship between earnings and housework, the economic exchange and gender display hypotheses. Our nonparametric model allows the relationships among earnings shares, earnings, and time spent on housework to emerge from the data. A second problem with earlier studies is that they have tended to draw uniform inferences across the range of data, including regions where the data are sparse. This has led to interpretations of parametric curves that are driven by these thinly populated regions, and that may not be robust across the data. By contrast, our study explicitly assesses the reliability of results obtained in such regions. Our results provide support for an alternative model that emphasizes the importance of partners' own earnings for their housework, especially in the case of women. Women's own earnings are negatively associated with their housework hours, independently of their partners' earnings and their shares of couples' total earnings, which do not matter.
Keywords: 330